Unraveling the complexity of therapeutic drug monitoring for monoclonal antibody therapies to individualize dose in oncology - Etienne Chatelut; Jeroen J. M. A. Hendrikx; Jennifer Martin; Joseph Ciccolini; Dirk Jan A. R. Moes (Wiley, 2021)
Abstract Monoclonal antibodies (Mabs) have become key drugs in cancer treatment, either as targeted therapies or more recently as immune checkpoint inhibitors (ICIs). The fact that only some patients benefit from these drugs poses the usual question in the field of onco‐hematology: that of the benefit of individual dosing and the potential of therapeutic drug monitoring (TDM) to carry out this individualization. However, Mabs present unique pharmacological characteristics for TDM, and the pharmacokinetic-pharmacodynamic relationship observed should be interpreted differently than that observed for conventional drugs and small molecules. This pharmacology practice review has been summarized from a public debate between the authors at the International TDM and Clinical Toxicology meeting in Banff, 2020, regarding the potential roles of TDM in the Mab/ICI setting.